The effect of real exchange rate misalignment on economic growth: Evidence from emerging markets - Abdullahil Mamun; Emrah Eray Akça; Harun Bal; Nazamul Hoque (Universitas Islam Indonesia, 2021)
Purpose – This study’s main purpose is to investigate the effect of real exchange rate misalignment on economic growth performance for 21 emerging markets from 1980 through 2016.Methods – The study individually measures the real exchange rate misalignment series for 21 emerging markets by using the single-equation approach and then estimates the effect of real exchange rate misalignment, undervaluation, and overvaluation on economic growth performance through dynamic panel system generalized method of moments approach.Findings – The study finds that the real exchange rate of emerging markets is significantly misaligned. The study also argues that any deviation of the real exchange rate from its equilibrium value impairs economic growth. The view that overvaluation erodes growth is customarily accepted, while a real undervaluation is found to be a growth deteriorating fact.Implication - From the policy perspective, policymakers should be cautious enough in setting exchange rate policies to check its sustained misalignments over time so that it can enrich the ability of concerned authorities to attain the growth target by using it as a policy instrument.Originality – The study is in response to the need felt for a common analytical framework for examining misalignment in the real exchange rate to make a more inclusive decision relating to its effects on the growth performance of emerging markets.